Vibrational Spectra of dipyridine 1Oxide Metal II Tetracyanonickelate Complexes - Karacan, Nurcan; Kantarci, Ziya; AKYÜZ, SEVİM (Elsevier, 1996)
Six new Hofmann-type complexes. M(pyridine-1-oxide)2(Ni(CN)4(M is Mn, Fe, Co, Ni, Cu, and Cd), have been prepared and their infrared and Raman spectra are reported. Effects of metal-ligand bond formation on the vibrational modes of pyridine-1-oxide are examined.
Keywords: Hofmann-type complexes; Metal-ligand bond formation; Vibrational spectra